Effect of moisture transfer on texture uniformity of cooked rice after heat preservation with electric rice cooker. (January 2020) - Zhang, Qingxia; Xia, Shuqin; Li, Jing; Zhang, Xiaoming; Yu, Jingyang
Abstract: The texture uniformity of rice cooked by electric rice cooker (ERC) will deteriorate during the heat preservation process. In this study, the uniformity of rice texture and water dynamic were investigated by means of physical property analyzer and low-field nuclear magnetic resonance technique. The water content, distribution and migration in rice were compared to illustrate the effect of heat preservation mode with different temperature at pot cover. The middle-upper layer of rice was drier and harder after 24 h of heat preservation in conventional mode, while the outer-upper layer of rice absorbed water, swelled or even broken. The difference of water content between the two parts was 6.55%, and the difference of hardness was 333.31 g. The relaxation signal indicated that the binding force between immobile water of the two parts and the rice matrix became weaker after heat preservation. By adjusting the heat preservation mode with higher temperature of the cover, the moisture content difference between the internal-upper layer and the peripheral upper layer was decreased to 0.39% after 24 h of heat preservation, and the hardness difference was reduced to 2.99 g. These mean that the texture uniformity of the whole pot rice after heat preservation was maintained. Graphical abstract: Image 1 Highlights: Water distribution of cooked rice after heat preservation by rice cooker changed. Water migration affects the uniformity of cooked rice texture. The modulation of pot cover temperature maintained the texture of cooked rice.